2015
DOI: 10.14697/jkase.2015.35.2.0333
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Verbal Interaction Patterns of Science-Gifted Students in Science Inquiry Activity

Abstract: This study analyzes the verbal interaction patterns used in a social network activity analysis that appeared in a science inquiry activity of 31 small groups of science-gifted students consisting of 5 members each. The results of this study are as follows: The interaction patterns showed eight types. The most prevalent interaction pattern, type 1, is triangle-shaped, interacting with 3 members out of 5 without a central member. Type 2 is wye form, interacting with 4 members and with one alienated member. Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Out of these, the changing interaction type was further divided into four subcases. Based on the criteria of dividing the type of interactions into alienated and participative type in a previous study (Kim & Kim, 2015), the changes of interactions in a small group were named as follows: the case in which the interactions did not change and the alienated member remained was named "alienation retaining type," and the four cases where the interactions changed were named "alienation expansion type," "alienation expansion returning type," "alienation participation expanding type," and "alienation participation switching type. "…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these, the changing interaction type was further divided into four subcases. Based on the criteria of dividing the type of interactions into alienated and participative type in a previous study (Kim & Kim, 2015), the changes of interactions in a small group were named as follows: the case in which the interactions did not change and the alienated member remained was named "alienation retaining type," and the four cases where the interactions changed were named "alienation expansion type," "alienation expansion returning type," "alienation participation expanding type," and "alienation participation switching type. "…”
Section: Resultsmentioning
confidence: 99%
“…The social network analysis method has been used in studies on interaction; however, they showed very limitation of study. For example, previous studies (Kim & Kim, 2015) analyzed the types of interactions that appeared in the inquiry activities using SNA. This study analyzed eight interaction types that appeared in inquiry activities.…”
Section: Verbal Interaction and Science-gifted Studentsmentioning
confidence: 99%
“…It helps in intuitively determining if any member plays a central role in the group or if there is an alienated member, and who the central or alienated member is . Kim and Kim (2015) analyzed the types of interactions occurring in inquiry activities through social network analysis. The study…”
Section: / 14mentioning
confidence: 99%
“…The previous study analyzed only small groups of five students and found that some students could not join the interaction. Based on this result, they suggested the research questions on the sample size which allows all students to join the interaction (Kim & Kim, 2015). Therefore, this study sought to analyze the characteristics of the interaction patterns of small groups of general students by adjusting the size of such groups.…”
Section: Eurasia J Math Sci and Tech Edmentioning
confidence: 99%
See 1 more Smart Citation